An electroactive single-atom copper anchored MXene nanohybrid filter for ultrafast water decontamination. Issue 46 (1st November 2021) - Jin, Limin; You, Shijie; Yao, Yuan; Chen, Hong; Wang, Yi; Liu, Yanbiao
Abstract : An electroactive and free-standing nanohybrid filter, consisting of single Cu atoms and MXene, enables ultrafast degradation of emerging contaminants. Abstract : Single-atom catalysts possess attractive electrocatalytic ability for degrading contaminants owing to their desirable characteristics compared with bulk counterparts. Herein, single Cu atoms anchored on Ti3 C2 T x MXene (Cu-SA/Ti3 C2 T x ) have been demonstrated as a highly reactive and robust nanohybrid filter for ultrafast removal of micropollutants via electro-peroxymonosulfate (PMS) activation. Sulfamethoxazole, a typical antibiotic, is observed to fully degrade via a single-pass through the nanohybrid filter (<150 ms) at 1.5 mL min −1 . Both experimental and theoretical studies verified that the Cu–O3 are the active sites for electro-PMS activation to produce 1 O2 and induce electron transfer for SMX degradation. As a result of the size effects, the HO˙ radicals dominate the SMX degradation process when anchoring Cu nanoparticles to the Ti3 C2 T x nanosheets. This study provides a proof-in-concept demonstration of the free-standing Cu-SA/Ti3 C2 T x nanohybrid filter that may find important applications in addressing the global problem of water pollution.